SARS-CoV-2 and changes in agricultural Economics and Agribusiness Student’s Life - Naranjo Retana, Amanda María (2021)
The objective of this article is to identify and analyze the changes in daily, labor, and academic life that have been perceived by the students of Agricultural Economics and Agribusiness of the University of Costa Rica (UCR) belonging to the Rodrigo Facio campus, South campus, and the enclosure of Guápiles, through the implementation of the virtual modality, on the methodological design. A sample of active students was selected, and an online survey was applied through the Google Forms tool. As a result of virtuality, the students have perceived affectation in aspects such as the mental and physical health. It was also evidenced that there are gaps that limit the inclusiveness of students to carry out their studies virtually.